Debt defaults and lessons from a decade of crises - Sturzenegger, Federico (MIT Press, 2006)
Providing case studies of debt defaults by Russia, Ukraine, Pakistan, Ecuador, Moldova, and Uruguay, framed by a discussion of the history, economic theory, legal issues, and policy lessons of sovereign debt crises, this work examines the facts, economic theory, and policy implications of sovereign debt crises.